CAREER DEVELOPMENT THROUGH COMPETENCY MOTIVATION AND EMPLOYEE PERFORMANCE - Yulianah (Sean Institute, 2022)
Efforts to develop jobs at PT Ewindo can be observed from the performance of employees. Employee performance, one of the prerequisites for employee success, is recommended by the leadership for career development. The purpose of this research is to identify the influence of motivation, competence, and performance on career development at PT Ewindo. Collecting data using a survey to 61 respondents. The analysis used is multiple regression analysis with SPSS. The results of the research prove that the motivation, competence and performance of employees have a positive influence on career development at PT Ewindo